2021
DOI: 10.3390/ma14030628
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Structure and Adsorption Properties of Mesoporous Silica Functionalized with Aminopropyl Groups by the Co-Condensation and the Post Grafting Methods

Abstract: The adsorptive potential has been evaluated for the aminopropyl functionalized mesoporous silica materials obtained by co-condensation and post grafting methods. Nitrogen sorption, small angle neutron and X-ray scattering (SANS and SAXS) demonstrated high surface area and well-ordered hexagonal pore structure suitable for applications as adsorbents of metals from waste waters. A comparison of Cr(VI) adsorption properties of the materials prepared by different functionalization methods has been performed. The o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…In the same situation, the amino-modified samples (SBA-15/APTES and SBA-15/PEHA) also maintained an intense (100) peak and weaker (110) and (200) peaks. The observation further confirmed that both SBA-15/APTES and SBA-15/PEHA maintained a hexagonally ordered structure after functionalization [ 27 ]. Figure 3 b presents an XRD pattern with a wide-range scan (2Θ = 10°–80°) of the SBA-15 sample.…”
Section: Resultssupporting
confidence: 65%
“…In the same situation, the amino-modified samples (SBA-15/APTES and SBA-15/PEHA) also maintained an intense (100) peak and weaker (110) and (200) peaks. The observation further confirmed that both SBA-15/APTES and SBA-15/PEHA maintained a hexagonally ordered structure after functionalization [ 27 ]. Figure 3 b presents an XRD pattern with a wide-range scan (2Θ = 10°–80°) of the SBA-15 sample.…”
Section: Resultssupporting
confidence: 65%
“…Synthetic silica based mesoporous materials, in spite of their higher costs, have also received wide attention and have been widely used for the adsorption of heavy metal ions due to their exceptionally large specific surface area, regular pore structure and suitability for surface modifications [ 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…With rises in contamination, many tactics for removing Cr (VI) have been developed, including biological approaches [ 12 ], electrochemical oxidation methods, membrane filtering methods [ 13 ], and adsorption methods [ 14 ]. The adsorption method is regarded as the most promising way of eliminating Cr (VI) due to its high efficiency, cheap cost, and simplicity.…”
Section: Introductionmentioning
confidence: 99%